2013
DOI: 10.1021/jf402253a
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic Extracts of Cynara cardunculus L. var. altilis (DC): A Source of Valuable Bioactive Terpenic Compounds

Abstract: Lipophilic extracts of Cynara cardunculus L. var. altilis (DC) from the south of Portugal (Baixo Alentejo) were studied by gas chromatography-mass spectrometry. One sesquiterpene lactone, four pentacyclic triterpenes, and four sterols were reported for the first time as cultivated cardoon components, namely, deacylcynaropicrin, β- and α-amyrin, lupenyl and ψ-taraxasteryl acetates, stigmasterol, 24-methylenecholesterol, campesterol, and Δ(5)-avenasterol. In addition, other new compounds were identified: ten fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
90
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 49 publications
13
90
0
Order By: Relevance
“…The extractives [22]. The high extractive content in cardoon stalks was mainly due to polar compounds (3.9 % of ethanol solubles and 4.3 % of water solubles), while the lipophilic compounds represented only a minor fraction (0.7 %), near to the range (1 to 2 %) previously reported [29]. The total lignin content in cardoon stalks was 19.2 %, a value slightly higher than the 17.0 % reported by Pereira et al [5], or the 16.4 % reported by Ballesteros et al [27].…”
Section: Chemical Characterization Of Cardoon Stalksmentioning
confidence: 56%
“…The extractives [22]. The high extractive content in cardoon stalks was mainly due to polar compounds (3.9 % of ethanol solubles and 4.3 % of water solubles), while the lipophilic compounds represented only a minor fraction (0.7 %), near to the range (1 to 2 %) previously reported [29]. The total lignin content in cardoon stalks was 19.2 %, a value slightly higher than the 17.0 % reported by Pereira et al [5], or the 16.4 % reported by Ballesteros et al [27].…”
Section: Chemical Characterization Of Cardoon Stalksmentioning
confidence: 56%
“…Recently, Ramos et al (2013) also reported for the first time in C. cardunculus L. var. altilis (DC) the presence of the following components: deacylcynaropicrin, lupenyl acetate and w-taraxasteryl acetate, the latter triterpene being the most abundant one.…”
Section: Triterpenes and Sesquiterpenesmentioning
confidence: 89%
“…6) were found to be the major class of lipophilic components of cultivated cardoon (Table 3). Sesquiterpenes are mainly concentrated in the leaves and present in low amounts in the stalks and capitula, in contrast triterpenes are present at lower amounts in the leaves (Ramos et al 2013). The authors also identified cynaropicrin as predominant sesquiterpene in the leaves.…”
Section: Triterpenes and Sesquiterpenesmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, the extraction of bioactive compounds could also be considered for an integrated valorization of Cca. Sesquiterpene lactones (SL) and pentacyclic triterpenes, the major constituents of Cca leaves and capitula lipophilic fractions [2] showed lower tryglyceride levels in rat serum [3] and anti-inflammatory [4] actions, respectively. Besides, cardoon extracts displayed antioxidant [5] and antitumor properties [6,7], mainly due to hydroxycinnamic acid derivatives.…”
mentioning
confidence: 99%